Water Splitting: A Hierarchical MoP Nanoflake Array Supported on Ni Foam: A Bifunctional Electrocatalyst for Overall Water Splitting (Small Methods 5/2018). Issue 5 (9th May 2018) - Jiang, Yuanyuan; Lu, Yizhong; Lin, Jianyi; Wang, Xin; Shen, Zexiang
Abstract : In article number1700369, Yizhong Lu, Zexiang Shen, and co‐workers report a novel MoP nanoflake array grown on nickel foam, which can act as high‐performance bifunctional electrocatalyst for water splitting. The bifunctional electrocatalyst behaves like two hands, one for the hydrogen evolution reaction (HER) and another for the oxygen evolution reaction (OER), respectively. With the two hands, the whole water splitting can be fulfilled efficiently.